Pengaruh Model Tipe Student Teams-Achievement Division (STAD) Oleh Guru Pendidikan Agama Kristen Terhadap Motivasi Belajar Siswa Di Kelas IX SMP Negeri 1 Ronggurnihuta Kab. Samosir Tahun Pembelajaran 2023/2024 - Yuli Setiawani Sipahutar; Risde Anakampun; Ronny Simatupang; Andar G Pasaribu; Megawati Manullang (Lembaga Pengembangan Kinerja Dosen, 2023)
The aim of this research is to determine the influence of the Student Teams-Achiement Division (STAD) type model by Christian Religious Education teachers on the learning motivation of class IX students at SMP Negeri 1 Ronggurnihuta Kab. Samosir TA. 2023/2024. The research method used is a quantitative method with a descriptive approach. The population was all 102 class IX students at SMP Negeri 1 Ronggurnihuta and a sample of 41 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 41 items, namely 24 items for variable motivating the learning of class IX students at SMP Negeri 1 Ronggurnihuta Kab. Samosir TA. 2023/2024: 1) Test analysis requirements: a) positive relationship test obtained by rxy = 0.459 > ​​rtable(a=0.05,n=41) = 0.308. b) Testing a significant relationship obtained a value of tcount= 3.226 > ttable(a=0.05,dk=n-2=39)= 2.021. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂=